A STUDY TO ASSESS THE PREVALENCE AND DETERMINANTS OF MALNUTRITION AMONG UNDER FIVE CHILDREN RESIDING IN THE SELECTED COMMUNITY, THIRUVALLUR DISTRICT - A, Florence Nightingale. K.; Sarathi, Sathiyalatha; Hemavathy, V.; I, Mahizh Punitha; B., Pandian; A, Jenifar Monisha (South Eastern European Journal of Public Health, 2025)
Introduction: Malnutrition among children under five years of age is a critical public health concern that has far-reaching implications for child health, development, and survival. This study aims to assess the prevalence and determinants of malnutrition among under five children residing in the selected community, Thiruvallur district Methods: This study is a cross-sectional survey using a convenient sampling method to assess malnutrition among under-five children in a selected community in Thiruvallur district, Tamil Nadu. A total of 100 children aged 0.5 to 5 years (6–59 months) will be included, based on availability and willingness to participate. Children who have lived in the community for at least six months and whose parents or guardians provide consent will be eligible. Those with chronic illnesses, congenital conditions affecting growth, or whose families do not consent will be excluded. Results: The findings revealed that children under five show suboptimal growth, with an average weight of 11.5 kg, height of 85.5 cm, and MUAC of 13.8 cm. Z-scores indicated nutritional challenges, including underweight prevalence (-1.0 WAZ), stunting (-1.2 HAZ), and wasting (-0.8 WHZ). Malnutrition was evident, with 20% of children being underweight, 15% stunted, and 10% wasted at moderate to severe levels. Conclusions: The study concluded that the findings of this study reveal a concerning prevalence of malnutrition among children under five, characterized by suboptimal growth and inadequate dietary practices.